2018
DOI: 10.1016/j.imlet.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

CD46 is a potent co-stimulatory receptor for expansion of human IFN-γ-producing CD8 + T cells

Abstract: Similar to CD4 T cells, precursor CD8 T cells are thought to depend on a co-stimulatory signal through CD28 for proliferation and differentiation into effector cells. CD46 is another co-stimulatory receptor that promotes differentiation of CD4 T-helper cells type 1 (Th1 cells) into a regulatory phenotype with a switch from IFN-γ towards IL-10-secretion over time. Whether CD46 exerts a similar function on CD8 T cells remains to be fully elucidated. Here, we demonstrate that CD46 co-stimulation induced secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…However, this study did not deplete CD56 + cells (natural killer (NK) and NK T cells) from their cultures, which impact heavily on CD8 + T-cell function, and could explain the discrepancy in observed outcomes of CD46 co-stimulation of CTLs between the two studies. This is supported by recent work published by Hansen and colleagues that confirms our finding as this group also observed increased IFN-γ secretion by human CTLs activated in the presence of anti-CD46 antibodies 37 . Cytotoxic activity, or CD46-driven downstream signals, however, were not explored in this work.…”
Section: Discussionsupporting
confidence: 93%
“…However, this study did not deplete CD56 + cells (natural killer (NK) and NK T cells) from their cultures, which impact heavily on CD8 + T-cell function, and could explain the discrepancy in observed outcomes of CD46 co-stimulation of CTLs between the two studies. This is supported by recent work published by Hansen and colleagues that confirms our finding as this group also observed increased IFN-γ secretion by human CTLs activated in the presence of anti-CD46 antibodies 37 . Cytotoxic activity, or CD46-driven downstream signals, however, were not explored in this work.…”
Section: Discussionsupporting
confidence: 93%
“…It has been observed that CD46 can induce low levels of IL-10 in CTLs, but the amounts generated are small compared to those observed in CD4 + /Th1 cells and a co-induction of suppressive activity in CTLs via CD46 was not investigated. 85…”
Section: The Complosome and Th1 Cell Contractionmentioning
confidence: 99%
“…Similarly, a role for CD46 or other complosome components during CD8 + T cell contraction remains to be investigated. It has been observed that CD46 can induce low levels of IL‐10 in CTLs, but the amounts generated are small compared to those observed in CD4 + /Th1 cells and a co‐induction of suppressive activity in CTLs via CD46 was not investigated . Nonetheless, intracellular complement can, analogously to what has been described in human CD4 + T cells, also exert negative control over CD8 + T cells.…”
Section: The Complosome In Human T Cell Metabolismmentioning
confidence: 99%
“…TCR and CD28 stimulation increases complosome activation and leads to autocrine engagement of CD46 also in these T cells (Figure 1B). However, and in contrast to CD4 + T cells, where CD46 signals are absolutely required for IFN-γ production and Th1 induction, in CD8 + T cells CD46 signals are not obligatory but rather support optimal CTL effector activity induced by TCR and CD28 engagement [12,53]. More specifically, in human CD8 + T cells, CD46 costimulation augments both CTL effector cytokine secretion (IFN-γ and TNF-α) and their ability to kill target cells, with concomitant increases in degranulation and granzyme B secretion.…”
Section: The Complosome and Ctl Activitymentioning
confidence: 99%
“…Similarly, a role for CD46 or other complosome components during CD8 + T cell contraction remains to be established. Of note, one study suggests that CD46 fails to drive IL-10 in CTLs, further underpinning differences in complosome activities between CD4 + and CD8 + T cells [53]. Nonetheless, there is indication that intracellular complement can, analogously to what is observed in CD4 + T cells, also exert negative control over CD8 + T cells to dampen CTL responses and prevent immunopathologies.…”
Section: The Complosome and Ctl Activitymentioning
confidence: 99%